Improvdent: Improving dentures for patient benefit. A crossover randomised clinical trial comparing impression materials for complete dentures - Gray Janine C; Navarro-Coy Nuria; Pavitt Sue H; Hulme Claire; Godfrey Mary; Craddock Helen L; Brunton Paul A; Brown Sarah; Dillon Sean; Dukanovic Gillian; Fernandez Catherine; Wright Jonathan; et al. (BMC, 2012)
Abstract Background According to the UK Adult Dental Health Survey (2009) 15% of adults aged 65-74, 30% aged 75-84 and 47% aged >85 years are edentulous and require complete dentures. Patients' quality of life and nutrition status are affected by poor dentures. The quality of the dental impression is the most important issue for improving the fit and comfort of new dentures. There is paucity of RCT evidence for which impression material is best for complete dentures construction. This study aims to compare two impression materials for effectiveness and cost effectiveness. Methods/Design IMPROVDENT is a double-blind crossover trial comparing the use of alginate and silicone, two commonly used denture impression materials, in terms of patient preference and cost-effectiveness. Eighty five edentulous patients will be recruited and provided with two sets of dentures, similar in all aspects except for the impression material used (alginate or silicone). Patients will try both sets of dentures for a two-week period, unadjusted, to become accustomed to the feel of the new dentures (habituation period). Patients will then wear each set of dentures for a period of 8 weeks (in random order) during which time the dentures will be adjusted for optimum comfort. Finally, patients will be given both sets of dentures for a further two weeks to wear whichever denture they prefer (confirmation period). Patients will be asked about quality of life and to rate dentures on function and comfort at the end of each trial period and asked which set they prefer at the end of the habituation period (unadjusted denture preference) and confirmation period (adjusted denture preference). A health economic evaluation will estimate incremental cost-effectiveness ratios of producing dentures from the two materials. A qualitative study will investigate the impact of dentures on behaviour and quality of life. Funding: IMPROVDENT is funded by NIHR RfPB (PB-PG-0408-16300). Discussion This trial aims to provide evidence on the costs and quality of dentures cast from two different commonly used impression materials; the intention is to significantly impact on the quality of denture production within NHS dentistry. Trial Registration ISRCTN Register: ISRCTN01528038 UKCRN Portfolio ID: 8305